A comprehensive review of topical hemostatic agents: The good, the bad, and the novel. Issue 1 (January 2020) - Tompeck, Allison J.; Gajdhar, Aniq ur Reham; Dowling, Matthew; Johnson, Steven B.; Barie, Philip S.; Winchell, Robert J.; King, David; Scalea, Thomas M.; Britt, L.D.; Narayan, Mayur
Abstract : ABSTRACT: Uncontrolled exsanguination remains the leading cause of death for trauma patients, many of whom die in the pre-hospital setting. Without expedient intervention, trauma-associated hemorrhage induces a host of systemic responses and acute coagulopathy of trauma. For this reason, health care providers and prehospital personal face the challenge of swift and effective hemorrhage control. The utilization of adjuncts to facilitate hemostasis was first recorded in 1886. Commercially available products haves since expanded to include topical hemostats, surgical sealants, and adhesives. The ideal product balances efficacy, with safety practicality and cost-effectiveness. This review of hemostasis provides a guide for successful implementation and simultaneously highlights future opportunities.